Time for kindness - Parent, Nancy; Ibrahim, Dalia Mohamed; Maruyama, Jerrod (Giza, Egypt nahdet misr publishing house, 2023)
Huey learns that being kind and helping others is much more fun than being stubborn and angry all the time
English stories
for child from 7 years to 10 years
Keywords: English stories